The quantum-field vacuum model of dark energy - Fomin, P.I.; Fomina, A.P. (Вопросы атомной науки и техники, 2013)
The gravitational mechanism of the radical reduction, comparing with the predictions of the local quantum field theory, of physical vacuum energy density is considered. It is shown that the account of self-gravitation of the quantum vacuum °uctuations decreases the total energy of fluctuations of the Planck size to zero, transforming them in topologically closed configurations. The total energy is defined as the positive self-energy of fluctuation plus the negative energy of its self-gravitation. By reasons of statistical physics, a hypothesis about the crystal-like ordering of the whole system of massless "Planck cells" is suggested. In this massless (or almost massless) crystal-like structure the subsystem of vacuum condensates with positive energy is integrated. The condition for the topological closure of Universe allows us to obtain an upper bound for positive energy density in the system close to the currently observed value. Розглянуто гравiтацiйний механiзм радикального зниження, порiвняннi з передбаченнями локальних квантових теорiй поля, величини густини енергiї фiзичного вакууму. Показано, що врахування самогравiтацii квантових флуктуацiй вакууму знижує повну енергiю флуктуацiй планкiвських розмiрiв до нуля, перетворюючиїх у топологiчно замкнутi конфiгурацiї. Повна енергiя визначається як власна позитивна енергiя флуктуацiї плюс вiд‘ємна енергiя її самогравiтацii. З статфiзiческiх мiркувань висувається гiпотеза про кристалоподiбне впорядкування всiєї системи таких безмасових "планкiвських комiрок". У цю безмасову кристалоподiбну структуру нiби влита пiдсистема вакуумних конденсатiв з позитивною енергiєю. Використання умови топологiчної замкнутостi Всесвiту дозволяє отримати оцiнку зверху для позитивної густини енергiї системи, близьку дозначень, що спостерiгались. Рассмотрен гравитационный механизм радикального понижения, по сравнению с предсказаниями локальных квантовых теорий поля, величины плотности энергии физического вакуума. Показано,что учет самогравитации квантовых флуктуаций вакуума понижает полную энергию флуктуаций планковских размеров до нуля, превращая их в топологически замкнутые конфигурации. Полная энергия определяется как собственная положительная энергия флуктуации плюс отрицательная энергия ее самогравитации. Из статфизических соображений выдвигается гипотеза о кристаллоподобном упорядочении всей системы таких безмассовых "планковских ячеек". В эту безмассовую кристаллоподобную структуру как бы влита подсистема вакуумных конденсатов с положительной энергией. Использование условия топологической замкнутости Вселенной позволяет получить оценку сверху для положительной плотности энергии системы, близкую к наблюдаемым значениям.